Answer:
See Explanation
Step-by-step explanation:
Your question is incomplete, as the equations or graph or table(s) were not given.
However, I'll give a general way of solving this.
Take for instance, the equations are:
![y = \frac{4}{3}x - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7Dx%20-%201)
![y = \frac{2}{3}x - \frac{1}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B2%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B2%7D)
To do this, we start by equating both equations.
![y = y](https://tex.z-dn.net/?f=y%20%3D%20y)
i.e.
![\frac{4}{3}x - 1= \frac{2}{3}x - \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%20-%201%3D%20%5Cfrac%7B2%7D%7B3%7Dx%20-%20%5Cfrac%7B1%7D%7B2%7D)
Collect Like Terms
![\frac{4}{3}x - \frac{2}{3}x= 1 - \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%20-%20%5Cfrac%7B2%7D%7B3%7Dx%3D%201%20-%20%5Cfrac%7B1%7D%7B2%7D)
Take LCM
![\frac{4x- 2x}{3}= \frac{2 - 1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4x-%202x%7D%7B3%7D%3D%20%5Cfrac%7B2%20-%201%7D%7B2%7D)
![\frac{2x}{3}= \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B3%7D%3D%20%5Cfrac%7B1%7D%7B2%7D)
Cross Multiply
![2x * 2 = 3 * 1](https://tex.z-dn.net/?f=2x%20%2A%202%20%3D%203%20%2A%201)
![4x = 3](https://tex.z-dn.net/?f=4x%20%3D%203)
Make x the subject
![x = \frac{3}{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B3%7D%7B4%7D)
Substitute 3/4 for x in ![y = \frac{4}{3}x - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7Dx%20-%201)
![y = \frac{4}{3} * \frac{3}{4} - 1](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B4%7D%7B3%7D%20%2A%20%5Cfrac%7B3%7D%7B4%7D%20-%201)
![y = 1 - 1](https://tex.z-dn.net/?f=y%20%3D%201%20-%201)
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
Hence:
![(x,y) = (\frac{3}{4},0)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%28%5Cfrac%7B3%7D%7B4%7D%2C0%29)
Answer:
x = StartFraction negative 2 plus or minus StartRoot 2 squared minus 4(4)(negative 1) EndRoot Over 2(4) EndFraction
Step-by-step explanation:
we know that
The formula to solve a quadratic equation of the form
![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
is equal to
![x=\frac{-b(+/-)\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%28%2B%2F-%29%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
in this problem we have
![4x^2 + 2x - 1=0](https://tex.z-dn.net/?f=4x%5E2%20%2B%202x%20-%201%3D0)
so
![a=4](https://tex.z-dn.net/?f=a%3D4)
![b=2](https://tex.z-dn.net/?f=b%3D2)
![c=-1](https://tex.z-dn.net/?f=c%3D-1)
substitute in the formula
![x=\frac{-2(+/-)\sqrt{2^2-4(4)(-1)} }{2(4)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-2%28%2B%2F-%29%5Csqrt%7B2%5E2-4%284%29%28-1%29%7D%20%7D%7B2%284%29%7D)
therefore
x = StartFraction negative 2 plus or minus StartRoot 2 squared minus 4(4)(negative 1) EndRoot Over 2(4) EndFraction
A^2 + B^2 = C^2
6^2 + B^2 = 7^2
36 + B^2 = 49
B^2 = 13
B = 3.61
Leave a like and a rating!
Answer:
c
Step-by-step explanation: